1986
DOI: 10.1126/science.2420009
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Granulocyte Colony-Stimulating Factor: Effects on Normal and Leukemic Myeloid Cells

Abstract: Experiments were conducted to isolate and characterize the gene and gene product of a human hematopoietic colony-stimulating factor with pluripotent biological activities. This factor has the ability to induce differentiation of a murine myelomonocytic leukemia cell line WEHI-3B(D+) and cells from patients with newly diagnosed acute nonlymphocytic leukemia (ANLL). A complementary DNA copy of the gene encoding a pluripotent human granulocyte colony-stimulating factor (hG-CSF) was cloned and expressed in Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
281
1
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,144 publications
(289 citation statements)
references
References 33 publications
6
281
1
1
Order By: Relevance
“…Numerous cytokines such as GM-CSF, IL-3, IL-6, IL-11, and SCF promote granulopoiesis by themselves and/or in concert with G-CSF [9,10]. G-CSF is indispensable for both steady-state and emergency granulopoiesis [11][12][13][14], and IL-17 regulates G-CSF secretion [9,10,[15][16][17][18]. In addition to Gr-1 1 cells, g/d T cells also participate in early protection against L. monocytogenes infection [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous cytokines such as GM-CSF, IL-3, IL-6, IL-11, and SCF promote granulopoiesis by themselves and/or in concert with G-CSF [9,10]. G-CSF is indispensable for both steady-state and emergency granulopoiesis [11][12][13][14], and IL-17 regulates G-CSF secretion [9,10,[15][16][17][18]. In addition to Gr-1 1 cells, g/d T cells also participate in early protection against L. monocytogenes infection [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…GM-CSF plays a crucial role in emergency, but not in homeostatic, hematopoiesis and is required for effective hematopoiesis during immune activation [74]. In contrast, IL-17 promotes G-CSF secretion, which plays a central role in proliferation and differentiation of Gr-1 1 cells in both normal and inflammatory conditions [9][10][11][12][13][14][15][16][17][18]. Since these cytokines participate in early protection against L. monocytogenes infection [14, 74-76, 89, 90], it is feasible that iNKT cells are a major source of these cytokines in protection against L. monocytogenes infection.…”
mentioning
confidence: 99%
“…It has been well known that AML cells frequently express G-CSFR [28][29][30][31][32][33][34] and their proliferation are often stimulated with G-CSF. 30,32,33 In contrast, Mirro et al 35 reported that ALL cells rarely respond to cytokines including G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a variety of non-haematopoietic malignant tumours, including bladder carcinoma (Welte et al, 1985a;Souza et al, 1986;Serve et al, 1991;Grammatico et al, 1993), have been confirmed to secrete G-CSF or GM-CSF (Wetzler et al, 1993) in amounts large enough to cause a significant systemic haematopoietic effect. Therefore, the leukaemoid reaction is a well-known paraneoplastic syndrome, which has been shown to arise from G-CSF and/or GM-CSF production by cancer cells (Wetzler et al, 1993).…”
Section: Discussionmentioning
confidence: 99%